Protective effect and antioxidative efficacy of Moringa stenopetala leaf extract in BV-2 microglial cell - Stephen Adeniyi Adefegha; Vitor Mostardeiro; Vera Maria Morsch; Ademir F. Morel; Ivana Beatrice Manica Da Cruz; Sabrina Somacal; Ganiyu Oboh; Maria Rosa Chitolina Schetinger (Food Chemistry Advances)
Moringa stenopetala is often consumed as food and used in folkloric medicine for the management of several diseases including neurodegenerative diseases. This study investigated the protective effect and antioxidant efficacy of aqueous extract of Moringa stenopetala in BV-2 microglial cells. Aqueous extracts of M. stenopetala were prepared, lyophilized and reconstituted in 0.5% dimethylsulphoxide (DMSO). Cells were treated with M. stenopetala extracts (0.1–100 µg/ml) for cell viability assay and nitric oxide (NO) production tests. However, M. stenopetala extract (50 µg/ml) was used in the treatment of cells for the determination of protein carbonyl content and reactive oxygen species (ROS) level. Incubation of BV-2 microglia cell with M. stenopetala extract maintained cell viability, diminished NO and ROS levels, and reduced protein carbonyl contents. Chlorogenic acid, rutin, kaempferol and quercetin derivatives were the main phenolic compounds identified in M. stenopetala leaf extract. In conclusion, this study suggests that M. stenopetala extract is rich in antioxidant and contains bioactive neuroprotective agents.